EVALUATION OF RESULTS FROM ARTHROSCOPIC REPAIR OF SLAP AT MILITARY HOSPITAL 175 - Nguyễn Hà , Ngọc; Võ Văn , Nguyên; Vũ Ngọc , Vương; Nguyễn Võ Sỹ , Trung; Bùi Chí , Khang; Từ Bảo , Ngọc (Journal of 175 Practical Medicine and Pharmacy, 2023)
Objectives: Evaluation of results from arthroscopic repair of SLAP at Military Hospital 175 Subjects and methods: Prospective study 25 patients for a SLAP lesion repair by arthroscopy, from January 2018 to December 2018. Result: With 25 patients for a SLAP lesion repair by arthroscopy, 40% SLAP lesion and 60% SLAP combined with another lesions. To include: 01 case dislocation AC joint, 01 case dislocation of shoulder, 13 cases rotator cuff tears. Results treatment: post-op mean at 4-5 days, results with UCLA 92% (good and exellent). Conclusion: SLAP lesion is Superior Labrum Anterior to Posterior tears. Arthroscopic repair of SLAP (suture labrum lesion) good treatment: post-op mean at 4-5 days, results with UCLA 92% (good and exellent). This study evaluate the preliminary results arthroscopic SLAP repair at 175 Hospital, they showed that shoulder arthroscopy is very important at dignosis and treatment SLAP combined with another lesions.